Amniotic membrane transplantation for ocular disease: a review of the first 233 cases from the UK user group. Issue 8 (21st February 2007) - Saw, Valerie P J; Minassian, Darwin; Dart, John K G; Ramsay, Andrew; Henderson, Hugo; Poniatowski, Stefan; Warwick, Ruth M; Cabral, Suzanne
Abstract : Background: Amniotic membrane transplantation (AMT), as a new tool in the armamentarium of therapies available for ocular surface problems, became widely available in the UK in 1998. This study evaluates the indications for treatment, the surgical procedures used, and the results of a subset of the first AMT cases carried out by the group using this nationally available supply. This user group model provides data which is different from that obtained from uncontrolled case series, or clinical trials, and may be more representative of the outcomes that can be expected when a procedure becomes widely available. Methods: The first 233 AMTs, performed by the UK user group, were evaluated by audit and outcomes were assessed at 3 months. Results: Of the 233 transplants, there were 126 (54.1%) valid outcome returns: the outcome for persistent epithelial defects was a healed and stable surface in 11/35 (31.4%, 95% CI 16.9 to 49.3); for chemical/thermal injuries, a healed uninflamed eye with clear cornea in 5/18 (27.8%, 95% CI 9.7 to 53.4); for bullous keratopathy a pain-free, stable surface without bullae in 4/18 (22.2%, 95% CI 6.4 to 47.6); for ocular surface reconstruction, an epithelialised uninflamed conjunctiva without scarring in 12/23 (52.2%, 95% CI 30.6 to 73.2); and for limbal stem cell deficiency, a corneal phenotype in 4/7 (57.1%). The operative technique least associated with failure was use of a bandage contact lens at the end of the procedure (OR 0.19, 95% CI 0.06 to 0.59, p = 0.004). Previous treatment with topical steroids was significantly associated with failure (OR 5.70, 95% CI 1.77 to 18.43, p = 0.004). Conclusion: Although the outcome criteria used in this study were stringent, and the follow-up duration was short, the results of AMT by this user group were generally less favourable than those of previously reported case series. Controlled clinical trials would improve the quality of evidence for use of amniotic membrane in ocular disease.